Women and NCDs: Overcoming the neglect - Ruth Bonita; Robert Beaglehole (Taylor & Francis Group, 2014)
Two in every three deaths among women are caused by non-communicable diseases (NCDs) - largely heart disease, stroke, cancer, diabetes and chronic respiratory diseases. The global discourse on health, however, largely views women in terms of their reproductive capacity, a persisting myth reflecting gender bias that shifts the focus away from NCDs, violence, and other injuries. Risk factors for NCDs are similar for men and women. Because fewer women actively smoke than men, and drink in less harmful ways, in most parts of the world, the impact of major NCD risk factors is far less in women than in men. In the area of diagnosis and treatment, gender bias can result in women being asked fewer questions, and receiving fewer examinations and fewer diagnostic tests for coronary heart disease and other NCDs compared with men with similar symptoms. In response to a UN meeting in September 2011, member states of WHO have agreed to a global goal to reduce avoidable NCD mortality by 25% by 2025 ('25 by 25'). A set of voluntary targets and indictors have been agreed upon, although none of them are gender specific. Most require changes at the policy level that will ensure that women - and children - will also benefit. As the 2015 deadline for the Millennium Development Goals approaches, women and NCDs should be central to the sustainable human development agenda.